Pengaruh Biosorben Cangkang Telur Ayam Terhadap Pemurnian Minyak Goreng Bekas - Dian Yanuarita Purwaningsih (Institut Teknologi Adhi Tama Surabaya, 2022)
One of the industries that need attention is the woven sarong industry. This industry produces liquid waste resulting from the coloring process. Indiscriminate disposal of waste will have a detrimental impact on the environment. Therefore, it is necessary to treat the waste first. The purpose of this study was to reduce the levels of COD and TSS in the colored liquid waste of the weaving sarong industry. This research uses the adsorption method using the adsorbent Zeolite activated by sulfuric acid. The concentration of sulfuric acid used was 2.5 N. The lowest COD removal percentage with a zeolite mass of 1 gram with a time of 60 minutes was 30.98% and the highest percent COD removal with a zeolite mass of 5 grams with a time of 180 minutes was 59.61% . The lowest percentage of TSS removal with a zeolite mass of 1 gram with a time of 60 minutes was 74.16% and the highest percentage of TSS removal with a zeolite mass of 5 grams with a time of 180 minutes was 94.05%.